The Role Of Shadow Teacher To Reduce Social Aggressiveness In Class 1 Students Elementary School - Mifta Wahyu Rafa Sakina; Dwi Sarwindah Sukiatni (Proceedings of The ICECRS, 2020)
This study aims to determine the role of the shadow teacher to reduce social aggressiveness in one grade 1 student of elementary schools. The approach used in this study is a qualitative approach to the type of descriptive research. The technique used to collect data is observation and interview techniques. The instruments used in this study were observation guidelines and interview guidelines. Data analysis was performed using data reduction, data presentation and conclusion drawing. Source triangulation is used as a test of the validity of the data used in this study. Qualitatively, the role of shadow teacher is very necessary for children who have problematic behavior, especially students who have social aggressiveness. The existence of a shadow teacher, students can feel cared for in the learning process so that students can participate in learning activities well in the classroom. In addition, students can also achieve learning outcomes in accordance with class demands and can follow their peers. The results showed that the presence of shadow teachers was quite effective in helping students reduce social aggressiveness in schools.